First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Liver-on-chip model and application in predictive genotoxicity and mutagenicity of drugs - B. Kopp; A. Khawam; K. Di Perna; D. Lenart; M. Vinette; R. Silva; T.B. Zanoni; C. Rore; G. Guenigault; E. Richardson; T. Kostrzewski; A. Boswell; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A placebo-controlled study of the effects of ayahuasca, set and setting on mental health of participants in ayahuasca group retreats - M. V. Uthaug; N. L. Mason; S. W. Toennes; J. T. Reckweg; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; K. van Oorsouw; J. Riba; J. G. Ramaekers (Psychopharmacology, 2021)
Ayahuasca is a plant concoction containing N,N -dimethyltryptamine (DMT) and certain β-carboline alkaloids from South America. Previous research in naturalistic settings has suggested that ingestion of ayahuasca can improve mental health and well-being; however, these studies were not placebo controlled and did not control for the possibility of expectation bias. This naturalistic observational study was designed to assess whether mental health changes were produced by ayahuasca or by set and setting. Assessments were made pre- and post-ayahuasca sessions in 30 experienced participants of ayahuasca retreats hosted in the Netherlands, Spain, and Germany. Participants consumed ayahuasca ( N = 14) or placebo ( N = 16). Analysis revealed a main effect of time on symptoms of depression, anxiety, and stress. Compared to baseline, symptoms reduced in both groups after the ceremony, independent of treatment. There was a main treatment × time interaction on implicit emotional empathy, indicating that ayahuasca increased emotional empathy to negative stimuli. The current findings suggest that improvements in mental health of participants of ayahuasca ceremonies can be driven by non-pharmacological factors that constitute a placebo response but also by pharmacological factors that are related to the use of ayahuasca. These findings stress the importance of placebo-controlled designs in psychedelic research and the need to further explore the contribution of non-pharmacological factors to the psychedelic experience.

Drug liking and wanting, not impulsive action or reflection is increased by 4-fluoroamphetamine - K. P. C. Kuypers; E. B. de Sousa Fernandes Perna; P. C. Dolder; S. W. Toennes; E. L. Theunissen; N. L. Mason; N. R. P. W. Hutten; J. G. Ramaekers (Psychopharmacology, 2018)

Subjective aggression during alcohol and cannabis intoxication before and after aggression exposure - E. B. De Sousa Fernandes Perna; E. L. Theunissen; K. P. C. Kuypers; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2016)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Rivastigmine but not vardenafil reverses cannabis-induced impairment of verbal memory in healthy humans - E. L. Theunissen; P. Heckman; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; A. Sambeth; A. Blokland; J. Prickaerts; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2015)

Monitoring and modelling land surface dynamics in Bermejo River Basin, Argentina: time series analysis of MODIS NDVI data - V. Barraza; F. Grings; M. Salvia; P. Perna; A.E. Carbajo; H. Karszenbaum (International Journal of Remote Sensing, 2013)

Performance of two commercial blood IFN-γ release assays for the detection of Mycobacterium tuberculosis infection in patient candidates for anti-TNF-α treatment - M. Bocchino; A. Matarese; B. Bellofiore; P. Giacomelli; G. Santoro; N. Balato; F. Castiglione; R. Scarpa; F. Perna; G. Signoriello; D. Galati; A. Ponticiello; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Model investigation about the potential of C band SAR in herbaceous wetlands flood monitoring - F. M. Grings; P. Ferrazzoli; H. Karszenbaum; M. Salvia; P. Kandus; J. C. Jacobo‐Berlles; Pablo Perna (International Journal of Remote Sensing, 2008)